Stereovision Co-Registration in Image-Guided Spinal Surgery: Accuracy Assessment Using Explanted Porcine Spines. Issue 6 (6th March 2018) - Evans, Linton; Olson, Jonathan D; Cai, Yunliang; Fan, Xiaoyao; Paulsen, Keith D; Roberts, David W; Ji, Songbai; Lollis, S Scott
Abstract: BACKGROUND: Current methods of spine registration for image guidance have a variety of limitations related to accuracy, efficiency, and cost. OBJECTIVE: To define the accuracy of stereovision-mediated co-registration of a spinal surgical field. METHODS: A total of 10 explanted porcine spines were used. Dorsal soft tissue was removed to a variable degree. Bone screw fiducials were placed in each spine and high-resolution computed tomography (CT) scanning performed. Stereoscopic images were then obtained using a tracked, calibrated stereoscopic camera system; images were processed, reconstructed, and segmented in a semi-automated manner. A multistart registration of the reconstructed spinal surface with preoperative CT was performed. Target registration error (TRE) in the region of the laminae and facets was then determined, using bone screw fiducials not included in the original registration process. Each spine also underwent multilevel laminectomy, and TRE was then recalculated for varying amounts of bone removal. RESULTS: The mean TRE of stereovision registration was 2.19 ± 0.69 mm when all soft tissue was removed and 2.49 ± 0.74 mm when limited soft tissue removal was performed. Accuracy of the registration process was not adversely affected by laminectomy. CONCLUSION: Stereovision offers a promising means of registering an open, dorsal spinal surgical field. In this study, overall mean accuracy of the registration was 2.21 mm, even when bony anatomy was partially obscured by soft tissue or when partial midline laminectomy had been performed.